Conceptualising Islamic Educational Management in the Era of Artificial Intelligence: A Multi-Case Synthesis of Neuro-pedagogy, Integrative Digital Leadership and Governance - Muhammad Riyadlul Jinan; Abdul Azizul Hakim (Journal Sophist, 2026)
Islamic education institutions in Indonesia, ranging from pesantren and madrasah to private Islamic higher education institutions (PTKIS), are adapting to artificial intelligence and platform-based learning without a shared framework for what a religiously grounded digital transformation should look like. This article addresses that gap by synthesising five recent field studies conducted between 2024 and 2026 across madrasah, pesantren, and PTKIS sites in Indonesia, supported by institutional documents and secondary case material. Using a qualitative multi-case synthesis design with thematic-narrative cross-case analysis, the study examines how neuro-pedagogical practice, digital leadership, value-based classroom management, conflict resolution, and total quality management interact under conditions of rapid digitalisation. Findings show that neuro-pedagogical competence combined with spiritual intelligence is the strongest predictor of innovative teaching performance, that leadership grounded in fathanah (wisdom) and shiddiq (integrity) determines whether digitalisation strengthens or erodes institutional legitimacy, and that musyawarah (deliberative consultation) is being reconceptualised as a moral-procedural-digital mechanism for resolving generational and administrative conflict. The study proposes a Triadic Sustainable Institutional Performance (SIP) model that positions neuro-pedagogy and spiritual intelligence as a cognitive-spiritual foundation, value-based management as a mediating layer, and integrative digital leadership, maqasid-anchored governance, and moral-procedural-digital musyawarah as three interacting pillars that jointly determine institutional outcomes. The article contributes a testable conceptual framework for Islamic education management research and offers practical guidance for institutional leaders navigating artificial intelligence adoption without treating digitalisation as a purely technical undertaking.